Sex Alters the MHC Class I HLA-A Association With Polyglandular Autoimmunity - Flesch, Brigitte K; König, Jochem; Frommer, Lara; Hansen, Martin P; Kahaly, George J (The journal of clinical endocrinology and metabolism, 2019)
Abstract Context The major histocompatibility complex (MHC) strongly contributes to the development of polyglandular autoimmunity (PGA). Objective To evaluate the impact of sex on human leukocyte antigen (HLA) association with PGA for the first time. Design Cross-sectional immunogenetic study. Setting Academic tertiary referral Orphan Disease Center for PGA (ORPHA 282196) and immunogenetics laboratory. Subjects Patients (158) with coexistent type 1 diabetes and autoimmune thyroid disease (adult type 3 PGA, ORPHA 227982) and 479 unrelated healthy controls. Interventions All 637 white subjects were typed for HLA-A, -B, -DRB1, -DQA1, and -DQB1 alleles at a two-field level. Main Outcome Measures Modification of the gene-disease association by sex. Results MHC class I HLA-A association was sex related to both the total white adult type 3 PGA collective (n = 158, P = 0.0065), as well as in PGA patients with autoimmune Hashimoto thyroiditis (n = 91, P = 0.010). Compared with HLA-A*02:01, A*11:01 was over-represented in male patients, yet under-represented in women (OR 1.49, 95% CI 0.55 to 3.88 vs 0.42, 0.12 to 1.17). A*24:02 was under-represented in male but not in female patients (OR 0.37, 95% CI 0.11 to 1.04 vs 1.19, 0.65 to 2.15). With the exclusion of the five most frequent alleles (A*01:01, A*02:01, A*03:01, A*11:01, and A*24:02), the sum of all other identified alleles was under-represented in male patients (OR 0.37, 0.18 to 0.72, P = 0.0046). The strong MHC HLA-B association with PGA (P < 0.0001) was not sex related (P = 0.55). Furthermore, no interaction with sex was observed for the MHC class II HLA-DRB1, -DQA1, and -DQB1 alleles. Conclusion MHC class I HLA-A association with type 3 PGA is significantly affected by sex. The typing of major histocompatibility complex class I and II alleles at a two-field level demonstrated for the first time a sex-related class I human leukocyte antigen-A allele association with adult type 3 polyglandular autoimmunity.